Functional conservation of the Sex-lethal sex determining promoter, Sxl-Pe, in Drosophila virilis. - Jinks, T.M.; Calhoun, G.; Schedl, P. (Development genes and evolution, 2003)
The primary sex determination signal in Drosophila melanogaster, the ratio of X chromosomes to autosomes, sets the activity state of the switch gene, Sex-lethal ( Sxl), by regulating the establishment promoter, m-Sxl-Pe. We have identified and characterized the establishment promoter, v-Sxl-Pe, of the distantly related species Drosophila virilis. Like melanogaster, the virilis Sxl-Pe is organized into four sub-domains: the Sxl-Pe mRNA leader and exon E1 of Sxl protein, the core promoter, the sex-specific element and the augmentation element. The core promoter and sex-specific element of v-Sxl-Pe show considerable sequence similarity to m-Sxl-Pe and contain target sites for components of the X/A signaling system. While the augmentation element of v-Sxl-Pe also has sequence motifs that could function as target sites for the X/A signaling system, it shows little similarity to the melanogaster augmentation element. Functional studies reveal that v-Sxl-Pe drives sex-specific expression in D. melanogaster embryos and that the activity of the virilis promoter is controlled by known components of the melanogaster X/A counting system. Although v-Sxl-Pe responds appropriately to the melanogaster sex determination signal, it is less active than Sxl-Pe from melanogaster. Unexpectedly, the reduced activity is due to differences in the activity of the conserved core promoter, while the non-conserved augmentation element functions effectively. These findings suggest that low-affinity target sites for the X/A counting system are critical for the functioning of Sxl-Pe.